Incidence, Knowledge, Attitude and Practice Toward Needle Stick Injury Among Health Care Workers in Abha City, Saudi Arabia - Alsabaani, Abdullah; Alqahtani, Norah Saeed S.; Alqahtani, Sarah Saeed S.; Al-Lugbi, Jawaher Hussain J.; Asiri, Malak Ali Saleh; Salem, Shyamaa Elsayed Elaraby; Alasmari, Ali Ahmed; Mahmood, Syed Esam; Alalyani, Mesheil (Frontiers in Public Health, 2022)
Background A needle stick injury is a serious occupational health hazard in health care settings. Health care workers are at risk of bloodborne diseases and the psychological consequences of these injuries. This study aims to estimate the incidence of needle stick injuries among healthcare workers during the previous 12 months and to assess their knowledge, attitude, and practice toward these injuries. Methods This cross-sectional study was conducted from 1st August 2019 till 15th February 2020, and included 786 healthcare workers in Abha city, Saudi Arabia. A structured questionnaire was used to collect the data. Results The incidence of needle stick injury among healthcare workers during the previous 12 months was (91/786) 11.57%. Nurses, females, and Saudis reported most needle stick injuries. More than half (52.7%) of the injuries went unreported. About 52.7% of needle stick injuries occurred during using sharp devices, and 42.9% of injuries happened in the patient room. The incidence of needle stick injury was significantly higher among those working at the secondary healthcare level (p = 0.003) and those practicing surgery (p < 0.001). Out of 786 participants, 94.7% knew the definition of needle stick injury, and 81.0% were aware of the procedure and guidelines to follow on sustaining a needle stick injury. Only 61.2% recognized that the recap of the needle is not recommended. Almost half of the participants (47.1%) agreed, and 33.6% strongly agreed that needle stick injury is preventable. A majority of healthcare workers (89.1%) had been vaccinated against Hepatitis B. Nearly 27.5% of healthcare workers incorrectly practiced recapping the needles with two hands and 8.7% bent needles before disposal. Recapping the needles was statistically significantly higher among healthcare workers who had a history of needle stick injury (p = 0. 046). Conclusion Needle stick injury and its under reporting among healthcare professionals is still a prevalent risk. Raising awareness among healthcare workers and improving the reporting systems for needle stick injuries to ensure more protection and early use of post-exposure prophylaxis is required. Implementation of safety precautions and safe injection practices and providing engineered safety devices may further reduce the risk.